Political reforms - "Panandiker Pai, V.A.(ed.)" (Delhi, 2001)
The present study attempts to identify the problems, analyses political,economic and systemic causes, examine policy options and suggest a concrete blueprint for political reforms of ensure sovereignty of the citizens. It covers matter such as structural reforms of the electoral system, citizen-state relationship, multilevel governance, criminalization, commutation, casteism,corruption, population control, poor administration, illiteracy, unrepresentative character of legislators, flaws in the organisation and functioning of political institutions,parties and electoral law and process, questionable conduct of legislators, instability of government etc.
Keywords: Political Reforms-India